Tissue flow cytometry immunophenotyping in the diagnosis and classification of non‐Hodgkin's lymphomas: A retrospective evaluation of 1, 792 cases1. Issue 2 (16th January 2013) - Demurtas, Anna; Stacchini, Alessandra; Aliberti, Sabrina; Chiusa, Luigi; Chiarle, Roberto; Novero, Domenico
Abstract: A retrospective analysis of 1, 792 solid tissues suggestive of lymphoma, submitted over a 12‐year period, was carried out and flow cytometry (FC) results were compared with histologic findings. The final histologic diagnosis of cases documented in this report is as follows: 1, 270 non‐Hodgkin's lymphomas (NHL); 17 composite lymphomas; four NHL plus carcinomas; five post‐transplant lymphoproliferative disorders; 105 Hodgkin's lymphomas (HL); eight acute leukemias; 42 tissue cancers; and 341 non‐neoplastic diseases. A strong correlation between morphology and FC data was observed among hematological malignancies (1, 268/1, 304, 97.2%) with the exception of HL. Among B‐NHL, FC detection of clonally restricted B‐cell allowed the identification of lymphomas that were not histologically clear and the differential diagnosis between follicular lymphoma and reactive hyperplasia. A high correlation level ( r = 0.83; P < 0.0001) was obtained in comparing proliferation results obtained by FC and immunohistochemistry. Among T‐NHL, FC detection of an aberrant phenotype direct histologic diagnosis in cases having less than 20% of neoplastic cells. In nine cases, FC suggested the need to evaluate a neoplastic population, not morphologically evident. Results show that FC routinely performed on tissue samples suspected of lymphomas is a fundamental adjunct to morphology in the diagnosis of NHL and may enhance the performance of the histologic evaluation so as to achieve the final diagnosis. To the best of our knowledge, this is the first report in the literature of a wide series of tissues also studied by FC. © 2013 International Clinical Cytometry Society